Rural Landscape Simplification and Provision of Cultural Ecosystem Services. A Case Study in the Argentine Pampas - Silvina María Cabrini; Estela Raquel Cristeche; Ignacio Raul Pace Guerrero; María Victoria Bitar (Economía Agraria y Recursos Naturales)
In recent decades, the rural landscape of the Argentine Pampas has undergone a process of simplification due to the increased land allocated to crops, replacing pastures and grasslands, with a substantial increase in soybean area. In 2016-2017, a survey was conducted to analyze changes in cultural ecosystem services in this region. Pergamino citizens relate landscape improvement in terms of aesthetic and recreational values to increasing its complexity since they prefer more winter crops, grazing areas, native vegetation, trees, and birds. The significant relationship between sociodemographic variables and preferences for landscape attributes is consistent with the notion that aesthetic perception is constructed from personal experiences and background.